A Cyclic Porphyrin Tetramer Linked by Azo and Butadiyne Bridges - Basic, Bruno; McMurtrie, J.; Arnold, D. (Wiley-VCH Verlag GMBH, 2010)
A soluble cyclic porphyrin oligomer (CPO) consisting of four5,10-diarylporphyrins linked by alternating azo and butadiynebridges has been synthesised via an aminated dinickel(II) butadiyne dimer. This is the first cyclic tetramerthat combines both azo and butadiyne bridges and extendsthe azoporphyrin family, which comprises only a very few examples. The electronic absorption spectrum of the tetrameris more similar to spectra of azoporphyrins than to thoseof butadiyne-linked dimers or tetramer, exhibiting a twocomponentSoret band with a splitting of 4190 cm–1 and astrongly red-shifted Q band maximum at 735 nm.